Effect of Differences in Protein Levels and Length of Fermentation Time on Physicochemical Characteristics of Caspian Sea Yoghurt Green Tea - Nabila Khairunnisa Mansoor,; Alvin Fajar Iqbal Faturohman,; Nabila Sekar Putri,; Lili Nailufhar,; M Iqbal Prawira-Atmaja,; Shinta Maharani,; Safitri, (JURNAL AGROINDUSTRI HALAL, 2024)
Caspian sea inoculum has been widely used for yogurt production, but it is rarely used in making green tea powder (GTP) yoghurt using milk with different protein content. This study aims to determine the changes in the characteristics of GTP yoghurt with Caspian sea inoculum using low fat UHT milk (SLF) or full cream UHT milk (SFC) during the fermentation period at 0 and 16 hours. The results showed that use of different types of UHT milk affected physicochemical characteristics. Fermentation for 16 hours caused a decrease in the pH of the sample to pH 4.3-4.4, but it was negatively correlated with an increase in the acidity. In addition, fermentation resulted increase the value of L* (brightness). The SLF sample has a greener color than the SFC sample. The viscosity of GTP yoghurt increased significantly at 16 hours in SFC and SLF samples. After 16 hours fermentation, the TPC became 4.15 mg GAE/g and 4.45 mg GAE/g with IC50 values ​​of 37.51 g/mL and 23.95 g/mL in SLF and SFC samples. The high protein content in UHT milk affected the high acidity, viscosity, and syneresis values ​​resulting a decrease in the TPC of GTP yoghurt.